2002
DOI: 10.1016/s0002-9440(10)64442-2
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulated Caveolin-1 Accentuates the Metastasis Capability of Lung Adenocarcinoma by Inducing Filopodia Formation

Abstract: Caveolin-1, a 21-to 24-kd protein, is the principal component of caveolae, which are special invaginated microdomains of the plasma membrane present in most mammalian cells. 1 It is well established that caveolin-1 is a tumor suppressor gene. Caveolin-1 mRNA and protein expression are frequently lost in human cancer cell lines. Re-expression of caveolin-1 in oncogenically transformed cell lines inhibits tumor cell growth and reduces tumorigenicity. [2][3][4][5][6] Several mechanisms have been proposed for cave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
154
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(172 citation statements)
references
References 25 publications
11
154
2
Order By: Relevance
“…Conflicting evidence exists for the role of caveolin-1 in anchorage-independent growth and invasion. While caveolin-1 inhibits anchorage-independent growth and invasion in 3T3 and MCF-7 breast cancer cells (Engelman et al, 1997;Fiucci et al, 2002), it increases the metastasis of lung adenocarcinoma (Ho et al, 2002) and esophageal carcinoma (Kato et al, 2002). This apparent contradiction may be related to its function as an inhibitor of apoptosis (Timme et al, 2000) and a promoter of survival/clonal growth and metastasis of prostate cancer cells (Li et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting evidence exists for the role of caveolin-1 in anchorage-independent growth and invasion. While caveolin-1 inhibits anchorage-independent growth and invasion in 3T3 and MCF-7 breast cancer cells (Engelman et al, 1997;Fiucci et al, 2002), it increases the metastasis of lung adenocarcinoma (Ho et al, 2002) and esophageal carcinoma (Kato et al, 2002). This apparent contradiction may be related to its function as an inhibitor of apoptosis (Timme et al, 2000) and a promoter of survival/clonal growth and metastasis of prostate cancer cells (Li et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…21,25,26 Previously, we and others found that expression of caveolin-1 (cav-1), the major component of caveolae, is elevated in prostate cancer and other malignancies. [27][28][29][30][31][32][33][34][35][36][37][38][39][40] To address the molecular mechanism of cav-1-mediated cell survival, we explored a possible link between cav-1 overexpression and Akt activation in prostate cancer cells. When we compared PI3-K-Akt signaling activities in cav-1-expressing LNCaP cells that had undergone adenoviral vector-mediated cav-1 gene transduction with PI3-K-Akt signaling activities in cav-1-negative vector control LNCaP cells, we found that Akt, but not PI3-K activities, were significantly higher in the former.…”
Section: Mechanisms Of Akt Regulationmentioning
confidence: 99%
“…In prostate, esophageal squamous cell carcinoma and lung carcinoma, expression of caveolin-1 correlates with increased metastasis and poor prognosis Li et al, 2001;Ho et al, 2002;Kato et al, 2002). In contrast, caveolin-1 is expressed in normal and benign ovarian epithelial cells and in normal colon mucosa, but is lost in serous ovarian carcinomas (Wiechen et al, 2001) and in colon carcinomas (Bender et al, 2000).…”
mentioning
confidence: 99%